Science and spirituality - Ryan, John A. (Mzuzu : Mzuni Press, 2016)
Science and Spirituality is an attempt to highlight the spiritual potential within the recent and on-going discoveries in both the science of the quantum world and the science of the larger cosmos. Science is now confirming what the mystics of former ages taught us. Somehow, these mystics, through silence and meditation, were able to discern and touch deep truths about what existence means. Abstract Algebra, which was once perceived as purely abstract with no practical application, is now at the heart of explaining existence within the quantum world. Thus mathematics, science and spirituality are just different faces of the same reality. This small booklet 'Science and Spirituality' merely introduces different aspects of this one reality which the author hopes to develop in more detail in further booklets.
6. Post Quantum Cryptography Research at Mzuzu UniversityChapter 8: Implications of the New Science; 1. The Relatedness of Everything; 2. A Participatory World; 3. Environmental Issues; 4. The GAIA Hypothesis; 5. A New Mindset; 6. New Revelation; 7. Redemption of All of Creation; Chapter 9: Our Response; 1. Celebrate through Rhythm and Dance; 2. Mathematics Having the Final Word; Back cover.
Online resource; title from PDF title page (viewed February 21, 2017).
Includes bibliographical references.
JSTOR
Keywords: Religion and science; Spirituality; Religion et sciences; Spiritualité.; RELIGION / Religion & Science; Religion and science; Spirituality; Religion -- Science